Not a Thing to Comfort You - Wortman-Wunder, Emily (Book collections on Project MUSE., 2019)
"From a lightning death on an isolated peak to the intrigues of a small town orchestra, the glimmering stories in this debut collection explore how nature - damaged, fierce, and unpredictable - worms its way into our lives. Here moths steal babies, a creek seduces a lonely suburban mother, and the priorities of a passionate conservationist are thrown into confusion after the death of her son. Over and over, the natural world reveals itself to be unknowable, especially to the people who study it most. In the words of a wildlife biologist, "you can take all of your measurements but I don't think they ever really tell you about what you need to know about the forest." Appealing to readers of Lydia Millet and Andrea Barrett, these tales of scientists, nurses, and firefighters catalog the loneliness within families, betrayals between friends, and the recurring song of regret and grief."--